Marranos the other of the other - Di Cesare, Donatella 1956- (Polity, 2020)
"Why the story of the exile is the heart of the modern condition"
Includes bibliographical references
Keywords: Geschichte 1391-2000; Marranen; Religiöse Verfolgung; Juden; Europa; Marranos / History; Jews / Europe / Persecution / History; Marranos; Europe; History